Associations of ultrafine and fine particles with childhood emergency room visits for respiratory diseases in a megacity. Issue 4 (22nd July 2021) - Fang, Jiakun; Song, Xiaoming; Xu, Hongbing; Wu, Rongshan; Song, Jing; Xie, Yunfei; Xu, Xin; Zeng, Yueping; Wang, Tong; Zhu, Yutong; Yuan, Ningman; Jia, Jinzhu; et al.
Abstract : Background: Ambient fine particulate matter with aerodynamic diameter less than 2.5 µm (PM2.5 ) has been associated with deteriorated respiratory health, but evidence on particles in smaller sizes and childhood respiratory health has been limited. Methods: We collected time-series data on daily respiratory emergency room visits (ERVs) among children under 14 years old in Beijing, China, during 2015–2017. Concurrently, size-fractioned number concentrations of particles in size ranges of 5–560 nm (PNC5–560 ) and mass concentrations of PM2.5, black carbon (BC) and nitrogen dioxide (NO2 ) were measured from a fixed-location monitoring station in the urban area of Beijing. Confounder-adjusted Poisson regression models were used to estimate excessive risks (ERs) of particle size fractions on childhood respiratory ERVs, and positive matrix factorisation models were applied to apportion the sources of PNC5–560 . Results: Among the 136 925 cases of all-respiratory ERVs, increased risks were associated with IQR increases in PNC25–100 (ER=5.4%, 95% CI 2.4% to 8.6%), PNC100–560 (4.9%, 95% CI 2.5% to 7.3%) and PM2.5 (1.3%, 95% CI 0.1% to 2.5%) at current and 1 prior days (lag0–1). Major sources of PNC5–560 were identified, including nucleation (36.5%), gasoline vehicle emissions (27.9%), diesel vehicle emissions (18.9%) and secondary aerosols (10.6%). Emissions from gasoline and diesel vehicles were found of significant associations with all-respiratory ERVs, with increased ERs of 6.0% (95% CI 2.5% to 9.7%) and 4.4% (95% CI 1.7% to 7.1%) at lag0–1 days, respectively. Exposures to other traffic-related pollutants (BC and NO2 ) were also associated with increased respiratory ERVs. Conclusion: Our findings suggest that exposures to higher levels of PNC5–560 from traffic emissions could be attributed to increased childhood respiratory morbidity, which supports traffic emission control priority in urban areas.